Casa Balla from the house to the universe and back - Dardi, Domitilla 1970-; Pietromarchi, Bartolomeo 1968- (Marsilio, 2021)
This volume presents the rearrangement of the interior of Giacomo Balla’s home in Rome curated by MAXXI and the interventions made in the museum by eight contemporary artists in dialogue with the legacy of the Futurist master
Impressum: "Casa Balla. From The House To The Universe And Back", 17 June - 21 November, 2021, MAXXI - National Museum of 21st Century Arts, Rome, Casa Balla Via Oslavia, Rome
Keywords: Balla, Giacomo -- 1871-1958; Künstlerhaus; Innenarchitektur; Haus; Architektur; Ausstellungskatalog -- Museo nazionale delle arti del XXI secolo -- 17.06.2021-21.11.2021 -- Rom